Adventures in 1,3-Selenazole Chemistry - Langer, Peter (Synlett, 2021)
The synthesis of 1,3-selenazoles and related compounds, including 2,4,5-trisubstituted, 2,4-disubstituted, 4,5-disubstituted, 4-substituted 1,3-selenazoles, and parent unsubstituted 1,3-selenazole, is highlighted. Emphasis is also given on 2-benzoyl-1,3-selenazoles which can be functionalized by Knoevenagel reactions or by rearrangements via their corresponding oximes. Syntheses of bis-, tris-, and tetrakis(1,3-selenazoles) are discussed as well. 1,3,4-6H-Selenadiazines are available from selenosemicarbazides and can undergo ring-contraction or deselenation reactions. Most syntheses rely on the application of selenocarboxylic amides, selenourea and related building blocks which are conveniently available by reaction of the corresponding oxygen analogues with P4Se10.1 Introduction2 Selenocarboxylic Amides3 2,4,5-Tri- and 2,4-Disubstituted 1,3-Selenazoles4 Bis(1,3-selenazoles)5 2-Amino-1,3-selenazoles6 2-Unsubstituted 1,3-Selenazoles7 1,3,4-Selenadiazines8 Conclusions
Keywords: cyclizations; heterocycles; nitrogen; regioselectivity; selenium